Optimizing pricing and ordering strategies in a three-level supply chain under return policy - Mahsa Noori-daryan; Ata Allah Taleizadeh (Journal of Industrial Engineering International, 2018)
This paper develops an economic production quantity model in a three-echelon supply chain composing of a supplier, a manufacturer and a wholesaler under two scenarios. As the first scenario, we consider a return contract between the outside supplier and the supplier and also between the manufacturer and the wholesaler, but in the second one, the return policy between the manufacturer and the wholesaler is not applied. Here, it is assumed that shortage is permitted and demand is price-sensitive. The principal goal of the research is to maximize the total profit of the chain by optimizing the order quantity of the supplier and the selling prices of the manufacturer and the wholesaler. Nash-equilibrium approach is considered between the chain members. In the end, a numerical example is presented to clarify the applicability of the introduced model and compare the profit of the chain under two scenarios.
Keywords: 650; Pricing; Ordering; Production; Return policy; Shortage; Nash-equilibrium game; Supply chain